Students' goals and self-regulation in the classroom - Marina Serra de Lemos (1999)
This chapter argues for an understanding of action regulation as inextricably related to the motivational process of goal setting and planning. Within this conceptual framework our research has explored students' action patterns, both in normal ongoing classroom situations and in stressful circumstances. Goals are emphasized as essential aspects of the motivational quality of activities, namely through the role they play in the regulation of action. In this study the detection of students' behavioral goals is addressed. Several achievement and social goals are described and ways to assess students' goal setting and planning processes are proposed. Strategies that students use to handle classroom stressors are explored. These include strategic flexible action, strategic rigid action, passive behavior, and disorganized behavior. These strategies represent distinct forms of action regulation. Relations between students' strategies, which are viewed as indications of their control, and agency beliefs are also examined. Finally, classroom features, which might help or hinder students' self-regulation are discussed, including teachers' goals and students' perceptions of teachers' goals for classroom activities. (c) 1999 Elsevier Science Ltd. All rights reserved.